2003
DOI: 10.1002/bjs.4308
|View full text |Cite
|
Sign up to set email alerts
|

Isolated hepatic perfusion with high-dose melphalan for the treatment of colorectal metastasis confined to the liver

Abstract: IHP for irresectable colorectal metastases confined to the liver resulted in good response rates and long-term survival in a selected group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 34 publications
3
33
2
4
Order By: Relevance
“…Results of these studies show response rates up to 74%, a median time to progression up to 14.5 months and a median survival of 27 months. Similar results were achieved with higher doses melphalan without TNF-a at the Leiden University Medical Center [74]. These data indicate that IHP for the treatment of non-resectable colorectal liver metastases can result in a considerable survival benefit.…”
Section: Isolated Hepatic Perfusionsupporting
confidence: 74%
“…Results of these studies show response rates up to 74%, a median time to progression up to 14.5 months and a median survival of 27 months. Similar results were achieved with higher doses melphalan without TNF-a at the Leiden University Medical Center [74]. These data indicate that IHP for the treatment of non-resectable colorectal liver metastases can result in a considerable survival benefit.…”
Section: Isolated Hepatic Perfusionsupporting
confidence: 74%
“…It is a demanding and surgically difficult procedure with considerable periprocedural morbidity of up to 37% including chemical cholecystitis, bile duct necrosis, veno-occlusive disease, bleeding and postoperative wound infection [3,6,9,10,12,14,18]. Conventional ILP, as described by the Leiden [9,10,13,14] and National Cancer Institute (NCI) [5,6,12] groups, consists of surgical clamping of the portal vein, the common hepatic artery and the inferior vena cava above and below the origin of the hepatic veins. Additional cannulae are placed in the gastroduodenal/proper hepatic artery and the retrohepatic inferior vena cava in order to create a perfusion circuit.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that IHP can effectively treat several types of liver metastases, resulting in a clear survival benefit compared with historical case series dealing with systemic chemotherapy [6][7][8][9][10][11][12]. However, IHP is a demanding, costly and difficult surgical procedure with considerable morbidity and mortality and, importantly, it is not amenable to repeat intervention mainly because of the formation of adhesions [6,9,10,[13][14][15]. Therefore, changes in procedural technique by avoiding a laparotomy and performing the whole procedure using a percutaneous approach, might result in lower procedural morbidity, operating time, overall cost and finally, it could make the procedure repeatable in the same patient, potentially resulting in a more powerful tool in the management of unresectable liver metastases [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have utilized multiple types of chemotherapy, including mitomycin C, oxaliplatin, and melphalan with and without TNFα [Zeh et al 2009;Alexander et al 2002Alexander et al , 2005Alexander et al , 2009Rothbarth et al 2003;van Iersel et al 2008avan Iersel et al , 2010.…”
Section: Colorectal Cancer Liver Metastasesmentioning
confidence: 99%